Coping with stress during the COVID-19 pandemic in the oldest-old population - Gerhards SK; Pabst A; Röhr S; Luppa M; Riedel-Heller SG (Springer Nature B.V., 2022)
The aim of the study is to investigate psychosocial factors that are associated with positive and negative coping with stress, as well as with worries about and perceived threat by COVID-19 to enable us to provide adequate support for oldest-old individuals. A paper–pencil-based survey assessed COVID-19 worries and perceived threat, depression, anxiety, somatization, social support, loneliness, resilience, positive and negative coping in a sample of n = 197 oldest-old individuals (78–100 years). Linear multivariate and binary logistic regression analyses were conducted. Individuals with high levels of resilience were more likely to feel self-efficient when coping with stress. High levels of depression, anxiety and loneliness were associated with feeling more helpless when coping with stress. However, oldest-old individuals who felt lonely also experienced situations where they felt competent in stress coping. Being male and experiencing high levels of social support was more likely associated with high levels of worries due to COVID-19. Increased age and higher levels of depression were associated with lower levels of perceived personal threat, whereas higher somatization scores were more likely associated with higher perceived personal threat. Findings suggest that mental health factors may shape the way oldest-old individuals cope with pandemic-related stress. Resilience might be an important factor to take into account when targeting an improvement in positive coping with stress. Oldest-old individuals who have higher levels of depression, anxiety and feel lonely may be supported by adapting their coping skill repertoire to reduce the feeling of helplessness when coping with stress.
Keywords: COVID-19 pandemic; Coping; Mental health; Old age; Public health; Stress